Graphic medicine and translation: acquisition of specialized knowledge and foreign language by german-spanish subtitling of videographies on vaccinology - Ramírez Almansa, Isidoro (Lenguas Modernas, 2021)
The present work aims to develop the digital competence of students and implement the use and knowledge of ICT tools in the classroom. This type of tools and competence have become even more important since the outbreak of the global pandemic of COVID-19 and the impact that it has had on the new reality of higher education teaching in Spain. Also, we intend that students learn and improve their knowledge of the German language while acquiring specialized knowledge, more speciically about medical language (vaccinology). To this end, we propose an activity that, as a summary, consists of subtitling ive videographies on vaccinology from German into Spanish. We also analyze how useful the translation and the subtitling process are, as well as the audiovisual product in the classroom and its beneits when learning a new language. Finally, we will assess the activity what will allow us to corroborate if we have fulilled the objectives we set, if our activity has been useful and if its design is adequate for the new teaching reality mentioned above.